Novel Methods of Diagnostics of Thyroid and Parathyroid Lesions - Ruchala, Marek; Szczepanek-Parulska, Ewelina (2022)
Thyroid nodular disease is one of the most frequent endocrine diseases. The prevalence of thyroid focal lesions detected by imaging techniques, according to studies on different populations, ranges from 10 to 70%. In a population of women over 50 years of age, approximately half of them will have a thyroid focal lesion. However, only 18% of thyroid nodules are diagnosed as malignant. Thyroid nodular disease is the most frequently diagnosed endocrine pathology, while thyroid cancer constitues the most common endocrine malignancy and is reponsible for about 67% of deaths due to neoplasms derived from endocrine organs. The incidence of thyroid cancer has risen by about 240% in the last three decades. Due to the increased availability of imaging techniques, recently, a rise in the detectability of thyroid cancer at the stage of microcarcinoma has been observed. Diagnostic and therapeutic decisions in patients with thyroid nodules require an interdisciplinary consensus between endocrinologists and physicians of other specialities (radiologists, pathologists, surgeons, oncologists). This book focuses on current trends in novel techniques of thyroid nodule diagnostics before they are implemented in the current guidelines on the management of thyroid nodular disease.